2022
DOI: 10.5377/calera.v22i38.14193
|View full text |Cite
|
Sign up to set email alerts
|

Sistemas silvopastoriles: una alternativa para la ganadería bovina sostenible

Abstract: La producción de alimento demanda cada vez el uso de mayor cantidad de recursos, lo que constituye un reto para los productores, investigadores e instituciones relacionados al sector agropecuario. Esto conlleva a realizar cambios en los procesos productivos al intensificar las áreas de producción sin sobre explotar los recursos naturales. El presente trabajo tiene como objetivo valorar la importancia de los sistemas silvopastoriles como una alternativa en los sistemas ganaderos, de cara a la transición agroeco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 12 publications
1
1
0
Order By: Relevance
“…GHG emissions in livestock production systems depend greatly on the characteristics of the herd and how it is fed (Yunga, 2020). This was confirmed in the present research, because animals have more options to select higher quality feed when they have more forage area, which would reduce methane emissions (Gutiérrez Bermúdez and Mendieta Araica, 2022). Numerous studies (López-Santiago et al, 2019;Carvajal and Andrade, 2020;Yunga, 2020), have confirmed that the use of SPS contributes to reducing GHG emissions from livestock farms.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…GHG emissions in livestock production systems depend greatly on the characteristics of the herd and how it is fed (Yunga, 2020). This was confirmed in the present research, because animals have more options to select higher quality feed when they have more forage area, which would reduce methane emissions (Gutiérrez Bermúdez and Mendieta Araica, 2022). Numerous studies (López-Santiago et al, 2019;Carvajal and Andrade, 2020;Yunga, 2020), have confirmed that the use of SPS contributes to reducing GHG emissions from livestock farms.…”
Section: Discussionsupporting
confidence: 79%
“…Numerous studies (López-Santiago et al, 2019;Carvajal and Andrade, 2020;Yunga, 2020), have confirmed that the use of SPS contributes to reducing GHG emissions from livestock farms. Here, we found that this reduction was on the order of 17%, which is a considerable step toward achieving the goals of returning to livestock as a mitigator of climate change (Schettini et al, 2021;Gutiérrez Bermúdez and Mendieta Araica, 2022). Despite this, some slight differences can be noted between states, which can basically be explained by the broad characteristics of SPS, which can vary in the abundance, type and size of perennial woody plants (Villanueva-López et al, 2015;López et al, 2019;Schettini et al, 2021).…”
Section: Discussionmentioning
confidence: 74%